ISO 14000 Environmental Management System and General Look on Turkish Construction Firms - TÜRK, AHMET MURAT (My University, 2011)
In recent years, the ISO 14000 environmental management system (EMS) has been widely used within all sectors throughout the world. There are some methods needed in order to maintain and develop the environmental performance within construction sector, for the protection of sustainable development and the environment worldwide and ISO 14000 EMS originated from such needs. Although an increased interest has emerged related to the use of the system in construction industry, the studies about the applications regarding the practice of the ISO 14000 EMS by the firms have not reached the desired level. In this study, the reasons for seeking ISO 14001 certification for the Turkish construction firms is being examined by using the questionnaire survey method. The obtained data through survey between the members of Turkish Contractors Association are analyzed in accordance with the objective of the study. According to the results of analysis, it is believed that no apparent and practical benefits exist for construction firms, initial and operating cost of certification are high and there is lack of knowledge and personnel related to ISO 14000. The high operation cost which is indicated as the most significant adversity in the implementation should be analyzed in detail by industry professionals and researchers. More studies are needed within the medium and small-scale firms. In the global construction market, an increase in the number of firms having EMS will both reduce environmental impact and develop the potential of awarding contracts to the construction firms from underdeveloped and developing countries.
Keywords: ISO 14000; Environmental management system; Environment; Standards; Construction